Constraints and challenges on inclusive education of children with Fragile X Syndrome - Franco, Vitor (2013)
Fragile X syndrome is the most common inherited cause of intellectual disability and the most known genetic cause of autism. Children with this syndrome have a set of cognitive and behavioral features, which put serious challenges to their full inclusion in the educational system. Intellectual disabilities, learning difficulties, hyperactivity, shyness and social anxiety are the most common of those behaviors. A qualitative study, using a Grounded Theory approach, was conducted to identify the main stages of the inclusion in mainstream schools, and also the constraints experienced in each one of these moments. An open interview was made with sixty parents of boys with Fragile X syndrome, and the data were analyzed in a Grounded Theory perspective, thought a coding process and categorization. The findings show that problems relating to inclusion tend to be progressively more serious over the course of education, and schools and teachers often experience great difficulties in providing educational environment and activities appropriate to the needs of children and families. In kindergarten years the inclusion is easier, although very often an adequate diagnosis is not already made. In elementary school the best success in inclusion appears to occur when there is a high commitment of the school, teachers and family in building solutions that promote child development. The good inclusion at this stage is mainly related to the child social skills, inclusive characteristics of school and commitment of the teachers. Progression to the further cycles of basic education brings new challenges resulting from changes in the educational organization. Quit school system is also a very important moment in this inclusion pathway. To know the main constraints experienced by children and families can help schools, teachers and policymakers to find the adequate solutions to the inclusion of these children and young with a genetic syndrome that is more and more frequent.